Cooperative assembly of redistributed arylgermanium-bearing alkoxysilanes in a mesostructured siloxane network. (29th July 2022) - Katir, Nadia; El Haskouri, Jamal; Amoros, Pedro; El Kadib, Abdelkrim
Abstract : Three redistributed arylgermanium-bearing mono-, bis- and tris-triethoxysilyl arms were designed, cocondensed with TEOS to access SBA-15-type materials and embedded in chitosan to prepare functional bioplastics. Abstract : In this contribution, three redistributed arylgermanium-bearing mono-, bis- and tris-triethoxysilyl arms were designed through metal-free radical-initiated hydrogermylation. Their cooperative assembly using amphiphilic Pluronic P123 afforded novel functionalized SBA-15-type materials with embedded arylgermanium in the silica walls. The formation of an ordered mesostructure depended to some extent on the bulkiness of the precursors and the experimental conditions. A nicely distributed germanium pattern was observed through elemental mapping along the siloxane framework, thereby providing a new rational design for stabilizing single atoms in a confined network. When introduced in an aqueous colloidal solution of polyglucosaminated chitosan, evaporative-induced co-assembly of the mixture enables the entrapment of arylgermanium-containing siloxane within the polysaccharide network with the simultaneous formation of transparent bioplastics. The occurrence of phase-separation resulted in texturally engineered polysaccharide–siloxane hybrid nanostructures.